PENGGUNAAN MEDIA AJAR BERBASIS MULTIMEDIA DALAM PEMBELAJARAN KANJI - Firmansyah, Dian Bayu; Rahmawati, Riska Sri (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2018)
This study aims to determine the effect of the use of teaching media kanji "Hyakugo" in improving the ability of mastery kanji JLPT level N5 learners. This study conducted with quasi experimental research methods with one group pre test-post test research design. Data collection conducted by survey questionnaires and interviews. Research subjects in this study were students from Department of Japanese Language Literature, Universitas Komputer Indonesia. The result of this study indicated that "Hyakugo" have a significant influence in term of enhancing learners kanji acquisition ability and improving students learning motivation. Furthermore, survey questionnaires feedback showed positive response from the learners, confirmed that "Hyakugo" is an interactive learning medium that helped them to maintain their learning motivation, user friendly and provides a lot of benefits for learners.